The Influence of Leadership in the Management of Organizational Decision Making - Nugroho, Tri Ambar; Cahyono, Firman Dwi; Anggiani, Sarfilianty (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Decision-making is one of the important management functions. Effective decision-making can help an organization to achieve its goals. Leadership is one of the factors that can affect the effectiveness of organizational decision-making management. The research method used is descriptive qualitative research. The data collection technique in this research uses a literature study. The data that has been collected is then analyzed thematically. Thematic analysis is done by identifying themes that are relevant to the research objectives. The results showed that leadership has a significant influence on the effectiveness of organizational decision-making management. Effective leadership can improve the effectiveness of organizational decision-making management through several ways, namely creating a participatory decision-making culture, improving communication and collaboration in the decision-making process, improving the quality of information available in the decision-making process, and increasing trust and support for decisions taken.